READABILITY OF TEACHING MATERIALS BY STUDENTS OF STABN SRIWIJAYA BASED ON FLESCH FORMULA - Suntoro Suntoro; Subyantoro Subyantoro; Rahayu Pristiwati (Philosophica: Jurnal Bahasa, Sastra, dan Budaya, 2022)
As prospective educators, students must have the competence to write good teaching materials. One indicator of good teaching materials is readability in accordance with the level of education of students. This study aims to determine the legibility of teaching materials by students using the Flesch Formula. The research method used is descriptive quantitative with instruments in the form of performance tests as a data collection tool. The results of this study indicate: (1) based on measurements using the Flesch Formula, 24% of teaching materials are in accordance with the specified readability level and 76% of teaching materials are not in accordance with the specified readability level; (2) A total of 17% of teaching materials are included in the category of moderately easy, 4% easy, 31% moderate, 24% quite difficult, 21% difficult, and 3% very difficult; and (3) other factors that cause incompatibility of teaching materials made by students are sentences that are too complex with the number only ranging from 2-7 sentences every 100 words. Therefore, prospective teachers should develop the skills of writing teaching materials well by practicing independently or under the guidance of the lecturer. Institutions can also make policies to deepen the writing of teaching materials for students in existing courses or insert new courses in the curriculum structure.